Nutritional profiling of some selected commercially important freshwater and marine water fishes of Bangladesh. Issue 10 (October 2022) - Ullah, Md. Rahamat; Rahman, Md. Arifur; Haque, Md. Nazmul; Sharker, Md. Rajib; Islam, M. Muhsinul; Alam, Md. Ariful
Abstract: The purpose of the study was to investigate the proximate composition and mineral content of Bangladesh's economically important freshwater and marine water fish. Proximate composition and mineral content was determined according to the Association of Official Agricultural Chemists (AOAC) standard method. All of the factors had a substantial variation ( p < 0.05), according to the findings. The maximum protein content was observed in Lates calcarifer (18.673%) and minimum in Pangasius pangasius (15.616%). The content of lipid among the species varied from 0.316% to 13.396%, with Mugil cephalus having the highest lipid content and Channa striata having the lowest. The moisture content ranges from 68.343% to 81.160%. All the fishes have an average ash content of 0.850%–4.350%. The energy content is also significantly higher in marine water fishes. The mineral content was highly variable. Calcium content was lowest in Pangasius pangasius (0.555%) and highest in Setipinna phasa (3.495%). The magnesium content ranged between 0.281% and 1.885%. Phosphorus was lowest in Lepturacanthus savala (0.826%) and highest in Setipinna phasa (2.114%). The amount of sodium, potassium, and sulfur was relatively less for all fish species but there were substantial differences across the twelve samples. The PCA biplot's for proximate composition analyses has demonstrated positive affinity only between Lates calcarifer and Mugil cephalus in case of ash, lipid, and carbohydrate whereas Setipina phasa, Mugil cephalus, Lutjanus lutjanus, and Oreochromis mossambicus were grouped together with magnesium, phosphorus, calcium, and sulfur in the case of mineral content. Overall, the marine water fishes can be a good food item in terms of nutrition which could provide better health benefits for human. Abstract : Proximate composition; Mineral content; Nutritive value; Freshwater; Marine water.